Особливості обліку та відображення у звітності інформації про забезпечення відповідно до національних та міжнародних стандартів, а також податкового кодексу України - Воськало, Н. М.; Карий, О. І.; Воськало, В. І.; Voskalo, N. M.; Karyj, O. I.; Voskalo, V. I. (Видавництво Львівської політехніки, 2017)
Розкрито окремі методичні прийоми ведення обліку забезпечень відповідно до національних та міжнародних стандартів, вимоги податкового законодавства для визнання створення забезпечень витратами, наведено пропозиції щодо вдосконалення ведення обліку забезпечень шляхом введення аналітичних рахунків з метою покращення інформації для формування фінансової звітності.

The need to accumulate resources to cover future expenses that are caused by the events of the present time, motivate the companies to create reserves in the form of provisions. Accounting of provisions is regulated by many accounting standards, as well as the Tax Code of Ukraine but needs further improvement in terms of determining the nature of provisions, methodological principles of creating and using. According to Methodical recommendations on accounting policy, there should be given a list of created provisions of future expenses and payments in accounting policy. Besides this list, there was suggested in the order about accounting policy, to describe in more detail the methods of evaluation of provisions, which creates enterprise in order to justify the value of recognized costs in the accounting. On the request of the State Fiscal Service, the expenses formation for the calculation of the financial results for corporate profit tax can only be processed on the basis of properly issued primary documents. Given the lack of legislatively established forms for provisions accounting, their creation should be formalized by primary documents, developed and approved by order of the company taking into account all the mandatory details. The carried out research and critical review of the scientific works of authors and current legislation stipulates the need for companies to use separate accounting sub-division of their long-term and ongoing support, which will enable to group high quality information for forming of financial reporting, including and using information systems. For a complete disclosure of information about provision, there should be provided in the Notes to annual financial reporting the additional information on designated purpose of provisions, reasons of uncertainty and the expected maturity term.
Peculiarities of the accounting and reflection of the information on provision in reporting in accordance with national and international standards, and tax code of Ukraine
Keywords: забезпечення; фінансова звітність; національні та міжнародні стандарти бухгалтерського обліку; податковий облік; provision; financial reporting; national and international accounting standards; tax accounting; 657.411.6